Réponses

  • Utilisateur Brainly
2014-09-08T20:29:03+02:00
6 - 2 * 5/4
= 6 - 10/4
= 24/4 - 10/4
= 14/4
= 7/2

11/7 - 9/7 * 5/3
= 33/21 - 45/21
= - 12/21

3/4 - 1/4 : 5/2
= 3/4 - 1/4 * 2/5
= 3/4 - 2/20
= 15/20 - 2/20
= 13/20

7/4 - 3/4 * (- 1/9)
= 7/4 - (-3/36)
= 63/36 + 3/36
= 66/36

2/3 - 5/3 * (1 - 1/5)
= 2/3 - 5/3 * 4/5
= 10/15 - 20/15
= - 10/15
= - 2/3

(5/6)² - 2/3
= 25/36 - 26/36
= - 1/36

(3 - 4 * 2/3) : 1/12
= (9/3 - 8/3) : 1/12
= 1/3 x 12
= 12/3
= 4

(5/6 - 2/3)²
= (5/6 - 4/6)²
= (1/6)²
= 1²/6²
= 1/36

5²/6 - 2/3
= 25/6 - 4/6
= 21/6